2010
DOI: 10.1200/jco.2009.21.8784
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Trial of Letrozole in Combination With Bevacizumab in Patients With Metastatic Breast Cancer

Abstract: Purpose Preclinical models suggest that the use of anti–vascular endothelial growth factor (anti-VEGF) therapy with antiestrogens may prevent or delay the development of endocrine therapy resistance. We therefore performed a feasibility study to evaluate the safety of letrozole plus bevacizumab in patients with hormone receptor–positive metastatic breast cancer (MBC). Methods Patients with locally advanced breast cancer or MBC were treated with the aromatase inhibitor (AI) letrozole (2.5 mg orally daily) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…However, some investigators adopted this approach and it was considered by some to be a minor violation. The feasibility and efficacy of administering bevacizumab in combination with letrozole, anastrozole, or fulvestrant were recently reported [14,15], and concomitant endocrine therapy with bevacizumab could plausibly have influenced efficacy outcomes in ATHENA. The ongoing randomized phase III LEA trial in Spain and Germany is comparing letrozole or fulvestrant alone or in combination with bevacizumab in post-menopausal women with previously untreated HER2-negative LR/mBC (ML19802; NCT00545077).…”
Section: Discussionmentioning
confidence: 98%
“…However, some investigators adopted this approach and it was considered by some to be a minor violation. The feasibility and efficacy of administering bevacizumab in combination with letrozole, anastrozole, or fulvestrant were recently reported [14,15], and concomitant endocrine therapy with bevacizumab could plausibly have influenced efficacy outcomes in ATHENA. The ongoing randomized phase III LEA trial in Spain and Germany is comparing letrozole or fulvestrant alone or in combination with bevacizumab in post-menopausal women with previously untreated HER2-negative LR/mBC (ML19802; NCT00545077).…”
Section: Discussionmentioning
confidence: 98%
“…Of the 43 patients evaluated, four patients had a partial response (PR) and 29 patients had stable disease (SD) for more than 24 weeks. Although the most common grade 3 side effects were hypertension and proteinuria (seen in 11 and 8 patients, respectively), overall the combination therapy of letrozole and bevacizumab appeared to be well tolerated [29]. Currently, a randomized, double-blind, placebo-controlled phase 3 trial of endocrine therapy alone or endocrine therapy plus bevacizumab (NSC 704865; IND 7921) is ongoing in patients with stage IIIB or IV hormone receptor-positive breast cancer to evaluate whether anti-VEGF therapy with bevacizumab can delay Ongoing the development of endocrine resistance and prolong PFS when added to first-line endocrine therapy.…”
Section: Trials Of Bevacizumab In Combination With Hormone Therapymentioning
confidence: 89%
“…As several phase II studies had suggested the feasibility and activity of the combination of bevacizumab with endocrine agents [50,51], a randomized phase III study (LEA) was conducted to test the hypothesis that anti-VEGF treatment with bevacizumab could prevent primary resistance to hormone therapy (either letrozole 2.5 mg/day or fulvestrant 250 mg/4 weeks) given as first-line therapy in endocrine responsive advanced breast cancer [52]. The PFS was better with the combination of bevacizumab plus endocrine therapy than with endocrine monotherapy (18.4 vs. 13.8 months), but this was not statistically significant.…”
Section: Ais and Anti-angiogenic Agentsmentioning
confidence: 99%